ILMIZI model in environmental learning during COVID-19: Improving students’ attitudes in University - Ilmi Zajuli Ichsan; Agung Purwanto; Henita Rahmayanti; Isil Koc; Merve Turan; Paulo Weslem Portal Gomes; Md. Mehadi Rahman; Lia Auliandari; Miza Nina Adlini; Irvan Permana; Helmia Tasti Adri (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Environmental education amid Coronavirus Disease 2019 (COVID-19) pandemic requires innovation. The pandemic situation need to improving student attitudes in maintaining the environment need an improvement by conducting various innovations and one of them is ILMIZI learning model utilization. The research aim was to improve student attitudes with the ILMIZI model. The research method is experimental without a control class. Samples involved in the research consist of 61 students with a treatment of environmental learning using the ILMIZI model. The Instrument used in this research was the attitude instrument with a scale of 1-5. The research results suggest that t-value (.231) > t-statistic (1.67) indicating that the ILMIZI model is not yet effective in improving the students’ attitudes in maintaining the environment. The pretest score (83.80) and post-test score (83.62) are not significantly different. The conclusion drawn from the research is that the ILMIZI model has not effective in improving student attitudes in maintaining the environment during COVID-19.